A229 THE USE OF INTRAVENOUS ALBUMIN IN PATIENTS WITH CIRRHOSIS: A RETROSPECTIVE ANALYSIS OF PRACTICE PATTERNS AT A TERTIARY CARE TEACHING HOSPITAL. (15th March 2019) - Rodrigues, D; Flemming, J
Abstract: Background: Intravenous (IV) albumin is a colloidal substance that is often used in the management of patients with cirrhosis. Current evidence-based guidelines support the use of albumin in Type 1 hepatorenal syndrome (HRS), large volume paracentesis (LVP) and spontaneous bacterial peritonitis (SBP). Physician surveys indicate that IV albumin is routinely used outside of recommended indications; however, little is known about the current prescribing indications in routine clinical practice. Aims: The aim of this study was to characterize the indications for which albumin was administered to patients with cirrhosis admitted to a tertiary care teaching hospital. Methods: We performed a retrospective cohort study of all patients with cirrhosis admitted to the Kingston Health Sciences Centre (KHSC) between January 1st and December 31 st, 2017. After electronic medical record review, those with a confirmed diagnosis of cirrhosis who received at least one dose of IV albumin were included. A detailed primary chart review was conducted and data was abstracted related to baseline demographics, disease related-characteristics, and the type and total dose of albumin prescribed. The indication for albumin was defined as HRS, LVP, or SBP based on recognized clinical criteria. Those not meeting criteria for these three conditions were considered to have albumin administered outside of clinical practice guidelines. Results: We identified 466 patients with cirrhosis admitted to KHSC and of those, 134 (29%) met inclusion criteria and received 173 total prescriptions for albumin. The median age was 62 years (IQR 56–69), 71% were male with a median length of stay of 10 days (IQR 7–19). The median MELD-Na score on admission was 22 (IQR 17–27). The most common causes of cirrhosis were alcohol-related (57 [43%])) followed by non-alcoholic fatty liver disease (27 [20%]) and hepatitis C (21 [16%]). The median dose of albumin administered per patient during the hospitalization was 125 grams (IQR 50–300 grams). Out of all the discrete instances where albumin was administered, LVP accounted for 30% of the cases, followed by SBP (10%), and HRS Type 1 (9%) while 51% had albumin prescribed outside of guidelines. Non-guideline indications for albumin administration included hypovolemia (17%), acute kidney injury not meeting HRS criteria (10%), sepsis (8%), paracentesis of less than 5L (1%), volume overload (1%) and hyponatremia (1%) – in the remainder of cases (13%), there was no clear indication identified. Conclusions: In a large, academic hospital, the use of IV albumin in patients with cirrhosis extended beyond current evidence-based guidelines in over 50% of cases. Given that evidence of the benefit of albumin does not exist in these settings, future studies evaluating the clinical benefits and costs of albumin use in these circumstances is warranted. Funding Agencies: CAG